2021
DOI: 10.3390/ijerph18010315
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Nutrient Intake, and Nutritional Status of Low-Income Students Attending a Brazilian University Restaurant

Abstract: In Brazilian universities, the university restaurant (UR) is essential in supporting students to complete their courses, as the UR offers free or low-cost food. In this sense, this research aimed to evaluate public policy effectiveness in offering food to low-income students attending the UR of the University of Brasília. This cross-sectional study compared low-income students (participating in the Student Assistance Program—Group 1) and students that did not participate in the Program (Group 2). Researchers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
3
1
4
Order By: Relevance
“…13 The daily dietary energy and cholesterol amounts of the students showed statistically significant differences according to their genders. While in a study, 14 the cholesterol intake of students was lower than this study, in a study conducted during the pandemic period, the pre-pandemic cholesterol intake of students was found to be similar to this study. 15 It has been observed that the consumption of foods of animal origin is high.…”
Section: Resultssupporting
confidence: 74%
“…13 The daily dietary energy and cholesterol amounts of the students showed statistically significant differences according to their genders. While in a study, 14 the cholesterol intake of students was lower than this study, in a study conducted during the pandemic period, the pre-pandemic cholesterol intake of students was found to be similar to this study. 15 It has been observed that the consumption of foods of animal origin is high.…”
Section: Resultssupporting
confidence: 74%
“…This could be because the staple foods in the northern part of Ethiopia are mainly cereals, known for its iron content. Furthermore, the average dietary iron intake for the university students from Brazil was also higher than what was found in the present study in both sexes (Hartmann et al, 2021).…”
Section: Average Dietary Energy and Nutrient Intakes Among Sport And ...contrasting
confidence: 84%
“…However, it is also important to find sustainable circular solutions as well as measuring the levels of food waste in mass consumption places and identifying the causes. Various studies have investigated plate waste in educational institutions (Hartmann et al , 2021; Qian et al , 2021). Furthermore, Boschini et al (2020), Garcia-Herrero et al (2021) and Conrad and Blackstone (2021) have studied plate waste and solutions in terms of sustainability.…”
Section: Discussionmentioning
confidence: 99%